تأثير الرضا الوظيفي على أداء العاملين بتوسط الولاء التنظيمي لدى بريد الجزائر بالوحدة الولائية للبريد بالنعامة (Revue El-Wahat pour les Recherches et les Etudes, 2025)
The Aim Of This Study Was To Find The Effect Of Employees Satisfaction On Performance By Mediating Organizational Loyalty By Identifying Elements Of The Employees Satisfaction . By Conducting A Field Study For The Employees Of Algeria Post, The State Unit In Naama, 80 Cases Of Usable And Analysis Were Analyzed Among 325 Employees.The Results Of Confirmatory Factor Analysis Have Found That Employees Satisfaction Has A Positive Effect On Organizational Loyalty And Organizational Loyalty Has A Positive Impact On The Staff Performance, And The Employees Satisfaction Has Indirect Impact On The Staff Performance, But Its Direct Effect Has Not Significant Statistically. Key Words- Staff Performance, Employees Satisfaction, Organizational Loyalty.